Public administration risks in the migration sphere in the context of digital transformation - V. Yu. Ledeneva; A. Kh. Rakhmonov (Управление)
The article considers the processes of digitalization of migration as a state policy aimed at improving the regulation of migration flows. The purpose of the study is to show the possibilities of digitalization of migration in Russia and at the international level, the positive aspects of this process and the main risks and threats arising during the implementation of digital technologies for making managerial decisions. The relevance of the study is associated with the necessity of introduction of digital technologies in the state management of migration processes. The paper reveals the concepts of digital transformation and the digital state. The authors note the difficulties that arise when trying to define digital technologies due to the unique and changeable social environment in which they are created. The study used systematic and comparative methods, content analysis of print and electronic media, analysis of scientific sources, which made it possible to study digital technologies as an object of state management of migration processes. According to the results of the analysis the paper concludes that digital transformation technology can influence the management of international migration in three different dimensions: 1) increase the gap between developed and developing countries; 2) contribute to the modernization of traditional methods used in the practices of international organizations; 3) influence the adoption of new, more informed management decisions in the field of migration to ensure border security. The authors reveal the main problems that developers of digital technologies and representatives of government bodies may face when mass implementing these technologies in migration practice. The conclusions of the article can be useful for interested government authorities involved in the regulation of migration processes.